The possibilities of combination immunotherapy with radiation therapy for the treatment of patients with inoperable locally advanced non-small cell lung cancer - E. I. Smolenov; G. V. Afonin; V. S. Usachev; D. D. Kudryavtsev; I. V. Kolobaev; S. A. Ivanov (Исследования и практика в медицине)
Currently, lung cancer is a global problem and public health issue in the world. Chemoradiotherapy remains the optimal method in the treatment of patients with unresectable non-small cell lung cancer (NSCLC). Nowadays, immune response checkpoint inhibitors (monoclonal antibodies) are actively introduced into clinical practice which demonstrated significant improvements in the overall survival for patients with unresectable NSCLC. These drugs block programmed cell death protein (PD‑1) and programmed cell death ligand 1 (PD-L1) that increases regulation on the surface of T-cells and improves the patient's immune system respond to tumor cells. In 2019, durvalumab was introduced into clinical practice for the treatment of patients with unresectable NSCLC (stage III) after chemoradiotherapy. In our study, we’ve summarizes studies investigated the feasibility and safety of radiotherapy with immunotherapy for locally advanced lung cancer.